2018
DOI: 10.1016/j.freeradbiomed.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

KRIT1 loss-of-function induces a chronic Nrf2-mediated adaptive homeostasis that sensitizes cells to oxidative stress: Implication for Cerebral Cavernous Malformation disease

Abstract: KRIT1 (CCM1) is a disease gene responsible for Cerebral Cavernous Malformations (CCM), a major cerebrovascular disease of proven genetic origin affecting 0.3–0.5% of the population.Previously, we demonstrated that KRIT1 loss-of-function is associated with altered redox homeostasis and abnormal activation of the redox-sensitive transcription factor c-Jun, which collectively result in pro-oxidative, pro-inflammatory and pro-angiogenic effects, suggesting a novel pathogenic mechanism for CCM disease and raising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 105 publications
10
87
2
Order By: Relevance
“…Heat shock proteins (HSPs), mainly functioning as chaperones, whose altered expression levels can result in misfolded proteins and lead to degradation. Up-regulation of both HSPA4 and HSPB1 was observed in CCM2 deficient HBMVEC lines, contradicting to previous report that CCM1 deficient cells have decreased levels of heat shock proteins (HSP, Hsp70 and Hsp27), which have a protective role in handling cellular stress 170 . DDB1, perturbed in all three CCMs-KD HBMVEC cells, is a part of the DDB1-CUL4 ubiquitin ligase complex, a key factor in autophagy.…”
Section: Protein Stability Regulation In Perturbed Csc Conditioncontrasting
confidence: 99%
“…Heat shock proteins (HSPs), mainly functioning as chaperones, whose altered expression levels can result in misfolded proteins and lead to degradation. Up-regulation of both HSPA4 and HSPB1 was observed in CCM2 deficient HBMVEC lines, contradicting to previous report that CCM1 deficient cells have decreased levels of heat shock proteins (HSP, Hsp70 and Hsp27), which have a protective role in handling cellular stress 170 . DDB1, perturbed in all three CCMs-KD HBMVEC cells, is a part of the DDB1-CUL4 ubiquitin ligase complex, a key factor in autophagy.…”
Section: Protein Stability Regulation In Perturbed Csc Conditioncontrasting
confidence: 99%
“…These discrepancies may be due to experimental differences (ie knockdown level, activation/inactivation of specific tyrosines on VEGFR2) and remain to be reconciled. Alternatively, recent reports have demonstrated a role for inflammatory signalling and oxidative stress in CCM lesion development, including the up‐regulation of the oxidative stress‐responsive transcription factor Nrf2, which indirectly promotes VEGF expression . Furthermore, Tang et al noted that activation of Toll‐like receptor‐4 (TLR4) signalling by blood‐borne gram‐negative bacteria led to greater CCM lesion burden in a mouse model of CCM .…”
Section: Discussionmentioning
confidence: 99%
“…23 These discrepancies may be due to experimental differences (ie knockdown level, activation/inactivation of specific tyrosines on VEGFR2) and remain to be reconciled. Alternatively, recent reports have demonstrated a role for inflammatory signalling and oxidative stress in CCM lesion development, including the up-regulation of the oxidative stress-responsive transcription factor Nrf2, 24 F I G U R E 5 Loss of CCM protein family members increases VEGFR2 tyrosine phosphorylation. A, Tyrosine phosphorylation of VEGFR2 in HPAEC transfected with negative control (NC), anti-KRIT1, anti-CCM2 and anti-CCM3 siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in CCM patient cohorts have led to the identification of three disease genes, CCM1/KRIT1, CCM2, and CCM3, which have been implicated in all major mechanisms of vascular integrity maintenance and endothelial barrier function, including the coordination of redox signaling and autophagy governing cell homeostasis and stress responses [43,[171][172][173][174][175][176][177][178][179][180]. Consistent with such pleiotropic functions, accumulated evidence from animal models and patient cohorts has demonstrated that loss-of-function mutations of CCM genes only predispose to the development of CCM disease.…”
Section: Vitamin D Deficiency and Ccm Diseasementioning
confidence: 99%